2015
DOI: 10.15446/caldasia.v37n1.50998
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTIVE BIOLOGY OF THE VENEZUELA ROUND STINGRAY Urotrygon venezuelae SCHULTZ FROM THE COLOMBIAN CARIBBEAN

Abstract: As for most batoid species, little is known about the basic biology of the Venezuela round stingray Urotrygon venezuelae (Urotrygonidae). This study presents information about the reproductive biology of the species, including fecundity, embryonic development stage, relationship between maternal size and fecundity, gonadosomatic (GSI) and hepatosomatic (HSI) indices, sex ratios, maturity size and size at birth. With all this information, a preliminary reproductive cycle is proposed. A total of 269 specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Both analysed species showed low fecundities, probably related to the aborted embryos observed of both species in the catches (e.g., Mejía‐Falla et al, 2012). However, these fecundities were consistent with the range reported for several species of the family Urotrygonidae (one to six embryos) (Acevedo et al, 2015; Alvarez‐Fuentes et al, 2023; Babel, 1967; Ehemann et al, 2022; Last et al, 2016). The maximum observed fecundity for U. rogersi in the present study was higher than that reported by Mejía‐Falla et al (2012) in Colombia (three embryos).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both analysed species showed low fecundities, probably related to the aborted embryos observed of both species in the catches (e.g., Mejía‐Falla et al, 2012). However, these fecundities were consistent with the range reported for several species of the family Urotrygonidae (one to six embryos) (Acevedo et al, 2015; Alvarez‐Fuentes et al, 2023; Babel, 1967; Ehemann et al, 2022; Last et al, 2016). The maximum observed fecundity for U. rogersi in the present study was higher than that reported by Mejía‐Falla et al (2012) in Colombia (three embryos).…”
Section: Discussionsupporting
confidence: 87%
“…This pattern in many species of elasmobranchs may be in part explained by the need for females to attain a larger size to support pups (Cortés, 2000(Cortés, , 2004Leung et al, 2023). However, this pattern was not evidenced in U. maculatus, probably due to the small size of this species (Pollom et al, 2020), which has also been suggested for some species of rays like the zipper sand skate Psammobatis extenta (Garman 1913) and the Venezuela round stingray Urotrygon venezuelae Schultz 1949 (Acevedo et al, 2015;Braccini & Chiaramonte, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…These American endemic round ray species are small‐ to medium‐sized stingrays (170‐ to 714‐mm TL), constituting one of the most abundant Eastern Pacific by‐catch batomorph species of the local and industrial shrimp fisheries (Last et al., 2016; Mejía‐Falla et al., 2011, 2012; Torres‐Huerta et al., 2015). The biological characteristics of several species of this family are unknown; however, biannual to triannual reproductive periodicity has been mentioned for some species of Urotrygon , with adult females having litters of up to six pups (Acevedo et al., 2015; Mejía‐Falla et al., 2012; Santander‐Neto et al., 2016). These particular aspects may result in a higher probability of producing specimens with morphological abnormalities, which has been hypothesized to be one of the primary explanations for the blue shark having the highest abnormality occurrence among shark species worldwide (Ehemann et al., 2016; Galván‐Magaña et al., 2011; Kanagusuku et al., 2020; Mancini et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…for some species of Urotrygon, with adult females having litters of up to six pups (Acevedo et al, 2015;Mejía-Falla et al, 2012;Santander-Neto et al, 2016). These particular aspects may result in a higher probability of producing specimens with morphological abnormalities, which has been hypothesized to be one of the primary explanations for the blue shark having the highest abnormality occurrence among shark species worldwide (Ehemann et al, 2016;Galván-Magaña et al, 2011;Kanagusuku et al, 2020;Mancini et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of the maturation process occurred at 175 mm L T with both ovary and liver increasing in mass. Liver mass is an important indicator of elasmobranch reproductive state (Ranzi, ; Acevedo et al ., ) and is the cause of overall mass increases (Kohler et al ., ), and the mass of pregnant females is higher than that of non‐pregnant females (Walker, ).…”
Section: Discussionmentioning
confidence: 99%